PROSES PENYIDIKAN TINDAK PIDANA PENCURIAN DENGAN PEMBERATAN YANG DILAKUKAN OLEH ANAK DITINJAU DARI UNDANG-UNDANG NOMOR 11 TAHUN 2012 TENTANG SYSTEM PERADILAN ANAK (Study Kasus Wilayah Polres Pasaman) - Ronaldo, Andreas (Menara Ilmu, 2018)
The process of investigating the crime of theft by a child's lawsuit, or in legal terms, is morecommonly known as the Child in Conflict with the Law (ABH) set out in Article 1 paragraph 2 ofLaw Number 11 Year 2012 on the Criminal Justice System of the Child.From the research resultgot the conclusion as follows: 1) The process of investigation of crime of theft with the severingdone by the child in Pasaman Police, has been done based on the provisions of CriminalProcedure Law in Indonesia that is Criminal Procedure Code, and Law Number 11 Year 2012About Criminal Justice System Child and Law Number 23 Year 2002 on Child Protection, it canbe seen from the procedure of investigator's action that the investigator of Pasaman Police inconducting an investigation on the criminal case of theft with child's obedience has been inaccordance with the rules of law which regulates the process of conducting an investigation ofchildren. 2) Obstacles in the process of conducting an investigation of criminal theft with theseverance committed by the child in Pasaman Police came from the suspect of the child, startingfrom the process of examining the crime scene, examination and handling. 2) Efforts to overcomeobstacles in the implementation of the process of investigation of criminal theft with the severingdone by the child in Pasaman Police is suspect did not want to participate when invited to thescene due to the fear of dealing with the society and the victim, conducted approaches to thecommunity and victims first by the investigator so that the suspect feels comfortable to come to thescene. Against the detention of a child's suspect during the investigator's detention proctorsometimes removes the child's suspect from the cell and invites to watch, and tells the story insidethe investigator's room. While the examiner conducted on the child, the suspect sometimes did notunderstand the question that the investigator submitted to him so that the investigator asks thehelp of the suspect's parents or guardian as well as escort officers to explain, during theexamination of the suspect the child is often bored and indifferent so the investigator sometimesstop the temporary inspection and let the suspect children play or watch for subsequentexamination.